2022
DOI: 10.3390/su14084526
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Effects of Consumer Satisfaction on Brand Switching Intention of Sharing Apparel

Abstract: Previous studies have found that consumer satisfaction is negatively associated with brand switching intention in the common purchasing context; is this still true in the context of sharing apparel? This study aims to investigate the effect of consumer satisfaction on the brand switching intention of sharing apparel and to reveal the mechanism by exploring the mediating effects of brand trust and platform trust, integrating the moderating effect of variety seeking. Data were acquired from 346 consumers of shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that product characteristics and external environment have a significant impact on consumers' brand preferences [33]. On this basis, our study separated the buyers and users from the consumer factors of infant formula compounding, and then refined the factor analysis of consumers' brand preferences.…”
Section: Brand Preference Theory Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that product characteristics and external environment have a significant impact on consumers' brand preferences [33]. On this basis, our study separated the buyers and users from the consumer factors of infant formula compounding, and then refined the factor analysis of consumers' brand preferences.…”
Section: Brand Preference Theory Model Constructionmentioning
confidence: 99%
“…The use cycle of infant formula is long, and the post-purchase behaviour is more critical for buyers' re-selection and infant formula manufacturers. If users respond well after purchase and promote the active purchasing behaviour of consumers, brand preference will be enhanced [33]. On the contrary, if buyers do not use it after purchase or users do not feel good after using it, brand preference will decrease, which is crucial for products with a long cycle and high brand loyalty.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Consumers who enjoy variety seeking actively seek out different brands to gain new experiences (Beldona et al, 2010). Niu et al (2019) explain that consumers' desire to experiment with products and services enriches their consumption experience, though this tendency varies among individuals (Wang & Xiao, 2022). In conclusion, variety seeking is a behavior that encourages consumers to explore products and services beyond their usual choices (LegohĂ©rel et al, 2012;Olsen et al, 2015).…”
Section: Theory Of Variety Seekingmentioning
confidence: 99%
“…Recently, studies have been conducted on the mediating role of the brand image between product quality and brand switching. (Abdelwahab et al, 2022;Wang et al, 2022;Sowunmi et al, 2022). Various credible research papers have also explored brand image as a mediator in this context (Saraswati et al, 2022;Helmi et al, 2022).…”
Section: Brand Image Mediates the Relation Between Product Quality An...mentioning
confidence: 99%